Nested Linear Mixed Models with Repeated Measurement for Analyzing Telecommunication Products: Model Linier Campuran Tersarang dengan Pengukuran Berulang untuk Menganalisis Produk Telekomunikasi - Fardilla Rahmawati; Khairil Anwar Notodiputro; La Ode Abdul Rahman (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2023)
Nested linear mixed model is a model that combines fixed factors and random factors. Observations made over time with the same object being observed are called repeated measurements. This research was conducted to determine the determinant factors of internet data quota sales which are influenced by SA (Sales Area), MC (Mutual Check), PC (Product Category), and time factors using a nested linear mixed model with repeated measurement. SA, PC, and time factors as fixed factors while the MC factor nested in SA as a random factor. The results showed that the interaction effect between three fixed factors, namely between SA, PC, and time have a significant effect on the sales volume of internet data quota. Moreover, variation in the sales volume between MC factors was significant. The interaction between MC and PC, and the interaction between MC and time were significant on the sales volume of internet data quota.